Redox status assessment in infertile patients with non‐obstructive azoospermia undergoing testicular sperm extraction: A prospective study. (13th November 2019) - Cito, Gianmartin; Becatti, Matteo; Natali, Alessandro; Fucci, Rossella; Picone, Rita; Cocci, Andrea; Falcone, Patrizia; Criscuoli, Luciana; Mannucci, Amanda; Argento, Flavia R.; Bertocci, Francesco; Serni, Sergio; et al.
Abstract: Background: Oxidative stress (OS) is one of the most prevalent causes of sperm damage, through the toxic effects of endogenously generated hydrogen peroxide, superoxide anion, and hydroxyl radicals. Peripheral leukocytes represent a feasible model for studying the pathophysiology of OS‐mediated homeostasis, which can be responsible for cell dysfunction and cell injury. Objective: To evaluate the redox status in patients with non‐obstructive azoospermia (NOA), establishing the potential role exerted by reactive oxygen species (ROS) in the genesis of testicular secretory injury. Material and methods: From May 2018 to March 2019, 39 patients were enrolled in this prospective single‐center cohort study and divided into two groups. Group 1 included 19 patients with NOA, and Group 2 included 20 normozoospermic men, partners of women with infertility tubal factor. All patients underwent serum blood tests. NOA underwent testicular sperm extraction (TeSE). ROS production (in lymphocytes, monocytes, and granulocytes) was assessed by fluorescence‐activated cell sorting (FACS) analysis. Plasma oxidative stress was evaluated by lipid peroxidation markers (MDA) and total antioxidant capacity (TAC) both assessed by fluorometric techniques. Results: Mean lymphocyte ROS production resulted 967.0 ± 224.5 vs 728.0 ± 98.0 (NOA vs Controls, P  < .001), monocyte ROS resulted 2102.5 ± 517.5 vs 1253 ± 171 ( P  < .001), and granulocyte ROS were 2366.5 ± 595.4 vs 1751.0 ± 213.0 ( P  < .001). Significant increases plasma lipid peroxidation markers were found in NOA patients compared with controls (2.7 ± 0.8 vs 0.37 ± 0.2 nmol/mL, P  < .001). Significant decreased TAC was evident in NOA compared with controls (13.4 ± 3.9 vs 3.0 ± 0.2 µmol/mL Trolox equivalents, P  < .001). No significant differences were found in blood leukocyte subpopulations ROS production, plasma lipid peroxidation, and TAC comparing groups (positive vs negative sperm retrieval, P  > .05). Conclusion: ROS production can be directly related to disorders of spermatogenesis, leading to severe conditions of male infertility, including azoospermia.